2018
DOI: 10.1093/sleep/zsy060
|View full text |Cite
|
Sign up to set email alerts
|

Sleep stage dynamics in neocortex and hippocampus

Abstract: Mammalian sleep comprises the stages of slow-wave sleep (SWS) and rapid eye movement (REM) sleep. Additionally, a transition state is often discriminated which in rodents is termed intermediate stage (IS). Although these sleep stages are thought of as unitary phenomena affecting the whole brain in a congruent fashion, recent findings have suggested that sleep stages can also appear locally restricted to specific networks and regions. Here, we compared in rats sleep stages and their transitions between neocorte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 40 publications
10
31
0
Order By: Relevance
“…Also noteworthy is that while fast spindle peaks were absent during REM at the scalp (in line with sleep scoring criteria), such peaks were sometimes observed in HPC ( Fig. 1DG), possibly related to asynchronous sleep stage transitions between brain structures (60,61). In contrast, REM beta power frequently showed a peak at the scalp, but generally not in HPC.…”
Section: Figure 1 Scalp and Hippocampal Sleep Spectrasupporting
confidence: 64%
“…Also noteworthy is that while fast spindle peaks were absent during REM at the scalp (in line with sleep scoring criteria), such peaks were sometimes observed in HPC ( Fig. 1DG), possibly related to asynchronous sleep stage transitions between brain structures (60,61). In contrast, REM beta power frequently showed a peak at the scalp, but generally not in HPC.…”
Section: Figure 1 Scalp and Hippocampal Sleep Spectrasupporting
confidence: 64%
“…However, such local sleep is not restricted to these animals. As new technology allows more brain regions to be examined simultaneously, it is becoming evident that even in conventional mammalian models for studying sleep, such as rodents and humans, traits used to define different states can occur at the same time in different brain regions (Nir et al, 2011, 2017; Vyazovskiy et al, 2011b; Emrick et al, 2016; Funk et al, 2016; Tamaki et al, 2016; Durán et al, 2018). Herein, we review the various types of local sleep found in birds, including those not known to occur in mammals.…”
Section: Introductionmentioning
confidence: 99%
“…Transition states are difficult to analyze because of their short duration and complexity. However, these periods are critical since they involve changes in multiple brain areas that are essential for the proper establishment of each sleep stage (Durán et al, 2018; Sánchez-López et al, 2018). One of these critical transition states is the slow-wave sleep (SWS) to rapid eye movement (REM) sleep transition.…”
Section: Introductionmentioning
confidence: 99%